A review of case-based reasoning in cognition–action continuum: a step toward bridging symbolic and non-symbolic artificial intelligence. (21st March 2013) - Öztürk, Pinar; Tidemann, Axel
Abstract In theories and models of computational intelligence, cognition and action have historically been investigated on separate grounds. We conjecture that the main mechanism of case-based reasoning (CBR) applies to cognitive tasks at various levels and of various granularity, and hence can represent a bridge—or a continuum—between the higher and lower levels of cognition. CBR is an artificial intelligence (AI) method that draws upon the idea of solving a new problem reusing similar past experiences. In this paper, we re-formulate the notion of CBR to highlight the commonalities between higher-level cognitive tasks such as diagnosis, and lower-level control such as voluntary movements of an arm. In this view, CBR is envisaged as a generic process independent from the content and the detailed format of cases. Diagnostic cases and internal representations underlying motor control constitute two instantiations of the case representation. In order to claim such a generic mechanism, the account of CBR needs to be revised so that its position in non-symbolic AI becomes clearer. The paper reviews the CBR literature that targets lower levels of cognition to show how CBR may be considered as a step toward bridging the gap between symbolic and non-symbolic AI.